Experience of Transformation: Church and Revolution (Czech Journal of International Relations, 2002)
Hans Maier: Revoluce a církev. K dějinám počátků křesťanské demokracie. 1. vydání. Brno: Centrum pro studium demokracie a kultury, 1999, 276 s., ISBN 80-85959-50-X.)